138 OUTCOME AND MORPHO-FUNCTIONAL CHANGES ON CARDIAC MAGNETIC RESONANCE IN PATIENT WITH ACUTE MYOCARDITIS FOLLOWING MRNA COVID 19 VACCINATION. (15th December 2022) - Palazzini, Matteo; Ammirati, Enrico; Lupi, Laura; Garascia, Andrea; Gentile, Piero; Pedrotti, Patrizia; Giannattasio, Cristina; Ciabatti, Michele; Rossi, Valentina; Ruschitzka, Frank; Uribarri, Aitor; Vecchio, Chiara; et al.
Abstract: Background: MessengerRNA (mRNA) COVID-19 vaccination has been associated with a higher-than-expected occurrence of acute myocarditis. Scarce information is available on mid-term prognosis and changes in cardiac function, volumes, and tissue characterization on cardiac magnetic resonance (CMR). Methods: Retrospective, multicenter study including patients with a definite diagnosis of acute myocarditis within 30 days from mRNA COVID-19 vaccination, with a confirmed myocarditis diagnosis based on endomyocardial biopsy (EMB) or autopsy or by the coexistence of positive biomarkers (troponin >99th upper reference limit or elevated creatine kinase myocardial band [CK-MB]) and cardiac MRI findings consistent with AM according to the 2018 updated Lake Louise Criteria. Results: 77 patients (median age 25 years [IQR 20-35], 15% female) were included and followed-up for 147 days [IQR 74-215]. Follow-up CMR was available in n=49 patients and showed no changes in biventricular ejection fraction (EF) as compared to CMR at diagnosis (left ventricular EF: 59%[55-65]vs. 60%[57-64], p=0.507, right ventricular EF: 56%[52-62]vs. 57%[52-61], p=0.563, respectively). Late gadolinium enhancement was present in all patients at diagnosis and persisted in only n=39 (79.6%) at follow-up (p=0.001), generally sparing the anterior wall and the septum. N=10 (20.4%) had a persistent edema based on T2-weighted short tau inversion recovery (STIR) sequences, with predominant involvement of inferior or inferior-lateral walls. The proportion of patients with increased T1 and T2 mapping signals significantly decreased at follow-up (n=13 (68%) vs. n=4 (13%), p<0.001, and n=21 (84%) vs. n=3 (10%), p<0.001, respectively), as well as the presence of pericardial effusion (n=16 (33%) vs. n=3 (6%), p=0.004). No differences in morpho-functional CMR parameters based on the type of vaccine administered were found (BNT162b2 Pfizer/BioNTech®, n=36, 73.5%, m-RNA-1273 Moderna®, n=13, 26.5%). Among patients with available follow-up (N=75, 97.4%), no major adverse cardiovascular events nor myocarditis recurrence or death were reported. Conclusions: At mid-term follow-up, patients who experienced an acute myocarditis after a mRNA COVID-19 vaccine had preserved biventricular EF. The rate and localization of residual scar or edema on CMR is in line with classic viral myocarditis with a good prognosis. This new piece of information should further reassure patients who experience acute myocarditis after mRNA COVID-19 vaccination.